77.3k views
1 vote
If f(x) = -x2 + 6x- 1 and g(x) = 3x2- 4x-1, find (f - g)(x).

User SethRocker
by
5.3k points

2 Answers

4 votes
ANSWER: (f-g) (x)= -4x2+10x
User Manas Kumar
by
5.3k points
6 votes

Answer:


(f-g)(x)=-4x^2+10x

Explanation:

We are given the two functions:


f(x)=-x^2+6x-1\text{ and } g(x)=3x^2-4x-1

And we want to find:


(f-g)(x)

This is equivalent to:


=f(x)-g(x)

Substitute:


=(-x^2+6x-1)-(3x^2-4x-1)

Distribute:


=-x^2+6x-1+(-3x^2+4x+1)

Rearrange:


=(-x^2-3x^2)+(6x+4x)+(-1+1)

Combine like terms. Hence:


(f-g)(x)=-4x^2+10x

User Marc Laugharn
by
4.9k points